Development of Problem Based Learning (PBL) practicum guide to improve student Creative Thinking Skills (CTS) in basic physics subject - Desrianti Sahida; Enny Zarvianti (Journal of Educational and Learning Studies, 2019)
The current study is research and development study, conducted based on observation results obtained from STKIP Muhammadiyah Sungai Penuh. 4-D model was applied in this study. The 4-D model consists of (1) define. Curriculum analysis was conducted, resulting in 48 credits obtained. Analysis on students was conducted, resulting in data revealing that the students’ creative thinking skills are still categorized as low. Analysis on subject matters was conducted, resulting in decision to implement the study in Basic Physics I subject matter.(2) design, where the preliminary practicum guide was obtained. (3) development, where the PBL-based practicum guide was categorized as 0.84% valid, 92.5% practical, 77% effective for cognitive aspects, competent for CTS improvements, 80% creative, 84% competent for attitudes and 84% competent for skills (4) dissemination, where the PBL-based practicum guide was categorized as 92% practical, 76.9% effective for cognitive aspects, competent for CTS improvements, 70% creative, 84% competent for attitudes and 86% competent for skills.